The impact of MTHFR 677C → T risk knowledge on changes in folate intake: findings from the Food4Me study. Issue 1 (December 2016) - O'Donovan, Clare; Walsh, Marianne; Forster, Hannah; Woolhead, Clara; Celis-Morales, Carlos; Fallaize, Rosalind; Macready, Anna; Marsaux, Cyril; Navas-Carretero, Santiago; San-Cristobal, Rodrigo; Kolossa, Silvia; Mavrogianni, Christina; et al.
Abstract Background It is hypothesised that individuals with knowledge of their genetic risk are more likely to make health-promoting dietary and lifestyle changes. The present study aims to test this hypothesis using data from the Food4Me study. This was a 6-month Internet-based randomised controlled trial conducted across seven centres in Europe where individuals received either general healthy eating advice or varying levels of personalised nutrition advice. Participants who received genotype-based personalised advice were informed whether they had the risk (CT/TT) (n = 178) or non-risk (CC) (n = 141) alleles of the methylenetetrahydrofolate reductase (MTHFR ) gene in relation to cardiovascular health and the importance of a sufficient intake of folate. General linear model analysis was used to assess changes in folate intake between theMTHFR risk, MTHFR non-risk and control groups from baseline to month 6 of the intervention. Results There were no differences between the groups for age, gender or BMI. However, there was a significant difference in country distribution between the groups (p = 0.010). Baseline folate intakes were 412 ± 172, 391 ± 190 and 410 ± 186 μg per 10 MJ for the risk, non-risk and control groups, respectively. There were no significant differences between the three groups in terms of changes in folate intakes from baseline to month 6. Similarly, there were no changes in reported intake of food groups high in folate. Conclusions These results suggest that knowledge ofMTHFR 677C → T genotype did not improve folate intake in participants with the risk variant compared with those with the non-risk variant. Trial registration ClinicalTrials.govNCT01530139